Gender-analysis on the modes of accommodation and resistance towards government programs against deforestation in Brgy. Abiera, Sebaste, Antique - Dionela, Leonaris D.
This study was undertaken to identify and determine the significant difference of the modes of accomodation and resistance between male and female and between abiera Development Association (ADA) members and non-members toward government programs against deforestation. the variables involved in this study were sex and membership in People's Organization (PO). Prospective program monitoring is the research design of the study. A surey interview was administered in the conduct of data gathering. The primary instrument used in this study was an interview schedule. The study found out that there was a significant difference in the modes of accomodation between male and female and between members and non-members toward government programs against deforestation. However, there was no significant difference in the modes of resistance between male and female and betwen members and non-members toward government programs against deforestation.